MicroRNA-100 Mediates Hydrogen Peroxide-Induced Apoptosis of Human Retinal Pigment Epithelium ARPE-19 Cells - Yuh-Shin Chang; Yo-Chen Chang; Po-Han Chen; Chia-Yang Li; Wen-Chuan Wu; Ying-Hsien Kao (MDPI AG, 2021)
This study investigated the regulatory role of microRNA 100 (miR-100) in hydrogen peroxide (H2O2)-induced apoptosis of human retinal pigment epithelial ARPE-19 cells. H2O2 induced oxidative cell death of cultured ARPE-19 cells was measured by cytotoxicity assay. qRT-PCR was used to quantify cytosolic and extracellular contents of miR-100. Kinase and miR-100 inhibition treatments were applied to determine the regulatory signaling pathways involved in cell death regulation. H2O2 dose-dependently reduced viability of ARPE-19 cells and simultaneously upregulated miR-100 levels in both cytosolic and extracellular compartments. Western blotting detection indicated that H2O2 elicited hyperphosphorylation of PI3K/Akt, ERK1/2, JNK, p38 MAPK, and p65 NF-κB. Further kinase inhibition experiments demonstrated that PI3K, p38 MAPK, and NF-κB activities were involved in oxidative-stress-induced miR-100 upregulation in ARPE-19 cells, while blockade of PI3K, JNK, and NF-κB signaling significantly attenuated the oxidative cell death. Intriguingly, MiR-100 antagomir treatment exerted a cytoprotective effect against the H2O2-induced oxidative cell death through attenuating the oxidation-induced AMPK hyperphosphorylation, restoring cellular mTOR and p62/SQSTM1 levels and upregulating heme oxygenase-1 expression. These findings support that miR-100 at least in part mediates H2O2-induced cell death of ARPE-19 cells and can be regarded as a preventive and therapeutic target for retinal degenerative disease.